The p75 Neurotrophin Receptor Facilitates TrkB Signaling and Function in Rat Hippocampal Neurons - Zanin, Juan P.; Montroull, Laura E.; Volosin, Marta; Friedman, Wilma J. (Frontiers in Cellular Neuroscience, 2019)
Neurotrophins activate Trk receptor signaling to support neuronal survival and many aspects of neuronal function. Early studies demonstrated that TrkA formed a complex with the p75 neurotrophin receptor (p75NTR), which increased the affinity and selectivity of NGF binding, however whether interaction of p75NTR with other Trk receptor performs a similar function to enhance ligand binding has not been demonstrated. We investigated the interaction of TrkB with full length p75NTR in hippocampal neurons in response to BDNF and found that the association of these receptors occurs after ligand binding and requires phosphorylation of TrkB, indicating that formation of this receptor complex was not necessary for ligand binding. Moreover, the interaction of these receptors required internalization and localization to early endosomes. We found that association of TrkB with p75NTR was necessary for optimal downstream signaling of the PI3K-Akt pathway, but not the Erk pathway, in hippocampal neurons. The absence of p75NTR impaired the ability of BDNF to rescue hippocampal neurons in a trophic deprivation model, suggesting that p75NTR facilitates the ability of TrkB to activate specific pathways to promote neuronal survival.